B Cell–Specific Loss of Lyn Kinase Leads to Autoimmunity - Lamagna, Chrystelle; Hu, Yongmei; DeFranco, Anthony L; Lowell, Clifford A (The Journal of immunology (1950), 2014)
The Lyn tyrosine kinase regulates inhibitory signaling in B and myeloid cells: loss of Lyn results in a lupus-like autoimmune disease with hyperactive B cells and myeloproliferation. We have characterized the relative contribution of Lyn-regulated signaling pathways in B cells specifically to the development of autoimmunity by crossing the novel lynflox/flox animals with mice carrying the Cre recombinase under the control of the Cd79a promoter, resulting in deletion of Lyn in B cells. The specific deletion of Lyn in B cells is sufficient for the development of immune complex–mediated glomerulonephritis. The B cell–specific Lyn-deficient mice have no defects in early bone marrow B cell development but have reduced numbers of mature B cells with poor germinal centers, as well as increased numbers of plasma and B1a cells, similar to the lyn−/− animals. Within 8 mo of life, B cell–specific Lyn mutant mice develop high titers of IgG anti–Smith Ag ribonucleoprotein and anti-dsDNA autoantibodies, which deposit in their kidneys, resulting in glomerulonephritis. B cell–specific Lyn mutant mice also develop myeloproliferation, similar to the lyn−/− animals. The additional deletion of MyD88 in B cells, achieved by crossing lynflox/floxCd79a-cre mice with myd88flox/flox animals, reversed the autoimmune phenotype observed in B cell–specific Lyn-deficient mice by blocking production of class-switched pathogenic IgG autoantibodies. Our results demonstrate that B cell–intrinsic Lyn-dependent signaling pathways regulate B cell homeostasis and activation, which in concert with B cell–specific MyD88 signaling pathways can drive the development of autoimmune disease.